Association of problematic internet use with health-related daily habits in adolescents: evidence from a school-based survey - Çelik, Esra; Oflu, Ayşe; Bükülmez, Ayşegül (The Turkish Journal of Pediatrics, 2025)
Background. With the development of technology, easier access to the internet and its excessive use have led to problematic internet use (PIU). The prevalence of PIU and its association with lifestyle behaviors in adolescents have become subjects of increasing academic interest. This study aimed to determine the prevalence of PIU among Turkish high school students and to investigate its association with sleep, physical activity and dietary habits. Methods. This cross-sectional study was conducted on high school students between October 2019 and March 2020. Participants completed a questionnaire regarding demographic characteristics, internet use, lifestyle habits and the “Young Internet Addiction Test-Short Form (YIAT-SF)”. Results. Among the total 951 participants, the mean age was 15.3±1.0 years, 42.3% were female, and the prevalence of PIU was determined as 12.1%. It was shown that having daily internet usage time ≥2 hours on weekdays, having at least one type of sleep problem, having breakfast less than 3 days per week, eating salty snacks ≥3 days per week, consuming sugary-carbonated drinks ≥3 days per week were associated with PIU. Conclusions. PIU is a widespread public health problem that is negatively associated with the daily health habits of adolescents. There is a need for nationwide school screening programs for this problem and rehabilitation of adolescents diagnosed with PIU.